Resource allocation scheme for IRS assisted heterogeneous SWIPT-NOMA system - JI Wei; LIU Ziqing (Tongxin xuebao)
Considering the heterogeneity of users to be served (different receiver structures) and the diversity of service requirements in the future large-scale Internet of things, an IRS-assisted simultaneous wireless information and power transfer (SWIPT) non-orthogonal multiple access (NOMA) communication system model for heterogeneous scenarios where power splitting (PS) users and time switching (TS) users coexist was proposed. Under the condition of satisfying the quality of service of the proposed scheme was better than other schemes two types of users, the transmit power of the base station was minimized by jointly optimizing the active beamforming of the base station, the passive phase shift matrix of the IRS, the power splitting ratio of the PS users, the time switching coefficient of the TS users and the successive interference cancellation decoding order of the two types of users. In order to solve the non-convex problem, an alternating iterative method based on successive convex approximation was used to split the problem into multiple sub-problems. For the passive beamforming optimization sub-problem of IRS phase shift, the sequential rank-one constraint relaxation approach was used to solve it. Simulation results show that the base station transmission power of the IRS-assisted communication system is significantly lower than that of the non-IRS scheme, the base station transmission power of IRS-assisted NOMA communication system is lower than that of IRS-assisted orthogonal multiple access communication system, the base station transmission power of the IRS-assisted PS-SWIPT system is lower than that of the IRS-assisted TS-SWIPT system.